(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The site of the study was ward of Narayan municipality of Dailekh district. This place is somewhat far from Narayan city interviewing with respondents, conclusions of the study are derived to increase the educational status of Badi community are it can be concluded that there are more nuclear families than the joint families. Few of them are still in joint family but it is breaking up due to mix society. Population of women is higher than males but age of marriage is lower than male. Early marriage is affecting to the education of Badi community. In the other hand, early marriage is punishable by the law but it is still remaining in the society. In this condition role of state is also important. People should be made aware by many ways. The literacy rate of Badi community has been increased by the adult education programs organized by Gas, NGOs, INGOs and government. Increasing consciousness of Badi community shows that if they get support by their family and given opportunity by the government to proportional representation they will achieve success. There is exclusion inside inclusion on the policy of the government. So, the opportunity should be given proportionally according to the population of every marginalized or backward caste and sex. Badi communities are solely dependent on agriculture. Female going out of home is negatively looked. This type of concept is one of the barriers breaking the every way of Badi community in achieving education. The social organizations should organize awareness programs. Society a social organization of working since many years ago, which has done many activities for their development but without supporting by the government it is less possibility of their achievement. Educational status depends upon economic status and the economic status depends upon socio-culture.